A taxonomic account of Myrcia (Myrtaceae) at the sites of the Biological Dynamics of Forest Fragments Project, Amazonas, Brazil - Gaem, Paulo Henrique; Lucas, Eve; Andrade, Ana; Vicentini, Alberto; Mazine, Fiorella Fernanda (Rodriguésia, 2022)
Abstract Myrcia is the sole genus of the Myrciinae, one of the nine subtribes of Myrteae (Myrtaceae). The Amazon forest holds about one-quarter of the Brazilian species of Myrcia, but the genus is still understudied in this whole region. In this context, this study presents a floristic survey of Myrcia in the permanent plots of the Biological Dynamics of Forest Fragments Project (BDFFP), in Amazonas state, Brazil. The genus is represented by 36 species in the study area, comprehending 32% of its total richness in the Brazilian Amazon forest, with 19 of them endemic to this domain. Myrcia neospeciosa is reported as a new occurrence for Amazonas state and M. grandis is recorded for the first time from upland terra firme forests on clayish soils. Myrcia cuspidata, a species with calyptrate flowers, is classified under Myrcia sect. Aulomyrcia, representing the second taxon of the genus with this feature removed from Myrcia sect. Calyptranthes. Finally, morphological aspects of the infra-generic categories of Myrcia are reported more overlapping than previously thought. A map containing the location of the study area, an identification key, descriptions, comments, and figures are provided. Resumo Myrcia é o único gênero de Myrciinae, uma das nove subtribos de Myrteae (Myrtaceae). A floresta amazônica detém cerca de um quarto das espécies brasileiras de Myrcia, mas este é ainda um gênero pouco estudado em toda a região. Neste contexto, este estudo traz um levantamento florístico de Myrcia nas parcelas permanentes do Projeto Dinâmica Biológica de Fragmentos Florestais (PDBFF), no estado do Amazonas, Brasil. O gênero é representado na área de estudo por 36 espécies, compreendendo 32% de sua riqueza total na Amazônia brasileira, com 19 delas endêmicas deste domínio. Myrcia neospeciosa é apresentada como uma nova ocorrência para o estado do Amazonas e M. grandis é registrada pela primeira vez na floresta de terra firme sobre solos argilosos. Myrcia cuspidata, uma espécie com flores caliptradas, é classificada em Myrcia sect. Aulomyrcia, sendo este o segundo táxon do gênero com esta característica removido de Myrcia sect. Calyptranthes. Por fim, notaram-se mais sobreposições entre os aspectos morfológicos das categorias infragenéricas de Myrcia do que anteriormente em outros trabalhos. São apresentados um mapa com a localização dos sítios de estudo, uma chave de identificação, descrições, comentários e figuras.